Galangin Suppresses Renal Inflammation via the Inhibition of NF-κB, PI3K/AKT and NLRP3 in Uric Acid Treated NRK-52E Tubular Epithelial Cells. (26th May 2019) - Lu, Hao; Yao, Hui; Zou, Rong; Chen, Xiwen; Xu, Hanlin
Abstract : Renal inflammation can result in renal injury. Uric acid (UA) is the final product of purine metabolism in humans and because of the lack of urate oxidase, UA may accumulate in tissues, including kidney, causing inflammation. Galangin was isolated from a traditional Chinese medicine plant and possesses several beneficial effects, working as an anti-oxidant, anti-mutagenic, anti-tumor, anti-inflammatory, anti-microbial, and anti-viral agent. Therefore, this study aimed at investigating the molecular mechanism of galangin in the attenuation of UA induced renal inflammation in normal rat kidney epithelial cells NRK-52E. Our findings suggested that galangin treatment efficiently protected NRK-52E cells against UA induced renal inflammation by decreasing tumor necrosis factor (TNF)- α, interleukin (IL)-1 β, IL-18, prostaglandin E2 (PGE2), and nitric oxide (NO) release, and it inhibited nitric oxide synthase (iNOS), prostaglandin endoperoxide synthase 2 (PTGS2), TNF- α, IL-1 β, and IL-18 mRNA expression. In addition, galangin was not exerting any cytotoxicity at the concentrations that were effective against inflammation as assessed by CCK8 assay. Moreover, western blotting showed that galangin treatment effectively inhibited nuclear factor-kappa B (NF- κ B), phosphatidylinositol 3 kinase (PI3K)/protein kinase B (AKT) and nucleotide-binding domain- (NOD-) like receptor protein 3 (NLRP3) signaling pathway activation. Taken together, these findings suggested that galangin plays a pivotal role in renal inflammation by suppressing inflammatory responses, which might be closely associated with the inhibition of NLRP3 inflammasome, NF- κ B and PI3K/AKT signaling pathway activation.